Hur energieffektiviserar man ett fartyg utan att göra tekniska modifikationer? - En fallstudie - Pettersson, Marcus; Sadeghi, Vahid (My University, 2017)
In this thesis we write a case study about how a shipping company with product tankers operatively work with energy efficiency. We address different barriers and solutions within the subject to give the reader an understanding to it. We also address some of IMOs measures and recommendations and how the company work with these. In this case study we get an example on that many of the barriers and solutions, is not always applicable and they are not always in the same extent as some articles wants it to be.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering